The article is devoted to the study of histochemical changes in blood plasma during inflammatory processes in children. (Eurasian Medical Research Periodical, 2025)
The article is devoted to the study of histochemical changes in blood plasma during inflammatory processes in children. The paper considers the main molecular and biochemical mechanisms that occur in the body in response to inflammation, as well as changes in the composition of blood plasma, such as levels of proteins, lipids, electrolytes and other biomolecules. Special attention is paid to histochemical research methods, which make it possible to study in detail the localization and activity of biochemical processes at the cellular level. Possible markers of inflammation that can be used in the diagnosis and monitoring of inflammatory diseases in children, including acute and chronic infections, autoimmune diseases, and allergic reactions, are being considered. The article provides an analysis of modern approaches to the treatment of inflammation and the role of histochemical changes in predicting the course of diseases